2018
DOI: 10.1002/sdtp.12431
|View full text |Cite
|
Sign up to set email alerts
|

43‐3: Distinquished Paper: Brilliant Cosmetic Film for Ambient Displays, with Cholesteric Liquid Crystal

Abstract: A brilliant cosmetic film with polymerized cholesteric material (PCM) has been developed. The film features a variety of colors by helical pitch gradients, diffusive texture, and arbitrary color patterns. It hides the display when turned off, and transmits display images when turned on. We believe it could change the display in the Off‐state from the conventional black wall to specially designed decorations. In addition, they can be applied to hidden sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…By controlling this pitch, various colors can be expressed 2 . As shown in Figure 1, our Ch‐LC films show the remarkable property of patterning colors by changing the helical pitch in the plane direction 3,4 …”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…By controlling this pitch, various colors can be expressed 2 . As shown in Figure 1, our Ch‐LC films show the remarkable property of patterning colors by changing the helical pitch in the plane direction 3,4 …”
Section: Introductionmentioning
confidence: 92%
“…In our previous study, we have found that Ch-LC can be given slightly wavy alignment by controlling the surface energy of the substrate. 3 As shown in Figure 4, since the wavy alignment reflects the light from various directions to one specific direction and the waveform is broadened, the color change of the reflection with change in viewing angle is reduced. 9 However, the average tilt angle of Ch-LC films was low (i.e., 4 ), and the reduction of color change was insufficient.…”
Section: Concept Of Reduction In Reflection Color Changementioning
confidence: 99%
See 3 more Smart Citations